An action research of student cognative english program: the online activity teaching strategy applications - Han-Kwang Chen (Big Data and Computing Visions)
The study aimed to examine difficulties encountered by higher education agencies through action research and to integrate "Online Activity" into an after-school english program at a university to optimize their teaching strategy. The study was conducted between October and December 2022. "Online Activity" was chosen as a possible optimization strategy because it assisted teachers in applying online activities to current course materials, improving students' learning motivations and learning outcomes. The results showed that online activity was a practical strategy for improving foreign language learning. Meanwhile, collaboration, discussions, and reflections among the action research team assisted professional development in teaching. The researchers recommend that educators choose appropriate action strategies to adapt to various learning situations, which may create opportunities for innovation in the current rigid education and learning environment.